PERI-IMPLANTITIS - A REVIEW OF ACTUAL TREATMENT METHODS - Francisc-Florin Bartok; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2016)
Dental implants have become a common solution in oral rehabilitation treatment, so prevention, identification and treatment of peri-implantitis treatment became a daily routine work for the specialists in oral implantology. Although, structures anchored on dental implants share similarities with natural dentition, such as biofilm and pathogenic factors acting at this level, periodontal treatment methods can be applied only partially, requiring a specific management of peri-implantar damage. The patient with of dental implants should be carefully educated about prevention methods and oral biofilm removal and prophylaxy, also regarding prosthetic restoration maintenance. Periodic checks will give the opportunity to identify early stage of peri-implantitis and give time for applying preventive and curative methods since early stage of peri-implantitis, maximising dental implant lifetime